Emerging patterns of manufacturing structural change - Haraguchi, Nobuya (UNIDO ViennaAT, 2011)
Aims to provide sound structural underpinnings for formulating industrial policy and to establish new development patterns at the manufacturing sector level based on a revised theoretical approach and available data, which stretches over 50 years.